A critical analysis of factors for delayed initiation of breast feeding in a district level hospital - M. V., Ramana Rao; Fathima, Naima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Breastfeeding is the cornerstone for child survival. Poor breastfeeding practices contribute to 20 per cent of neonatal deaths and nearly 13 per cent of deaths in children below five years. In south Asia, 40% of the babies are initiated breastfeeding within one hour despite increase in institutional deliveries, 80%. Methods: This prospective study was conducted to critically analyse the factors for delayed initiation of breast feeding. A prospective study was carried out among randomly selected postnatal mothers in the postnatal ward of a district teaching hospital. Data was collected by face to face interviews using a pre-validated structured questionnaire. Results: Above 90% of the women did not know the importance of initiating breast feeding within one hour of delivery as none of them received antenatal counselling. Baby was not given to the mother in 90% of the cases. 70% believed that colostrum is not good for the baby. 60% gave pre-lacteal feeds and 60% reported pain of surgical site or perineum as the cause for delayed initiation of breast feeding. Conclusions: UNICEF estimates that if all children receive the benefits of breastfeeding – globally, 8,23,000 child deaths can be averted every year. All health care facilities should adopt Baby Friendly Hospital Initiative’s Ten successful steps for breast feeding to initiate early breast feeding within one hour to reduce morbidity and mortality of infants and under five children.